Social Function of â€œRice for Poorâ€ on Poor Family - Setyo Sumarno (Jurnal Penelitian Kesejahteraan Sosial, 2015)
The research was conducted to provide certainty â€œrice for poorâ€ program can provide social protection to the poor. Some of the conditions that must be comply with the objektives of â€œrice for poorâ€ program were right in target, amount, quality, price, time, and administration, better known as 6 T. The research result showed that they found irregularities suchas Bagito case (Shared each other equally), change in unit targets, indicators of poverty, and a lack of valid data, so the indicators of 6 T success yet to be realized. Referring to the problems mentioned above, it was clear that to achieve the 6 T indicators inâ€rice for poorâ€ program itself still can not be achieved, that was still far to the main objective of socialprotection that should cover: to prevent and reduce the risk of human experience to avoid severe and prolonged misery; to increase the willingness of vulnerable groups to face and out of poverty, misery and social-economic insecurity; to allow the disadvantaged groups to have a dignified standard of living so that poverty will not be passed on from one generationto another. To achieve the desired objectives needed for improvement in both social protection and distribution of â€œrice for poorâ€ quota mechanism, data problem, poverty indicators, the efforts to provide social protection to low-income people need to be reformed, especially with the meaning of social protection associated with the quota of rice for the poor, rice quality, delivery mechanisms, the problem of data, anda indicators of poverty.